An integration of UPLC‐Q‐TOF/MS and chemometrics analysis for the holistic quality evaluation of different geographical Paederia scandens. (3rd May 2022) - Zhang, Zhiyong; Peng, Le; Chen, Yuru; Zhang, Kun; Chen, Junhui; Li, Zheng; Li, Wenlong
Abstract : Rationale: Due to the special geographical location and climate of China, there are large differences in the chemical composition and content of Paederia scandens (PS) from different origins, which will have a large impact on its efficacy. Methods: An efficient quality control method for PS was established by combining ultra‐high‐performance liquid chromatography (UPLC) and electrospray ionization mass spectrometry analyses. First, a UPLC‐quadrupole time‐of‐flight mass spectrometry system was employed to identify the chemical composition of PS from seven different origins. Then, the chemical variation in 73 batches of PS samples was subsequently investigated by quantitation of four marker compounds. Results: A total of 15 common compounds were identified in the samples of PS from seven origins. And four of the marker compounds were chosen based on VIP values to characterize the differences between PS samples of different origins. The linearity ranged between 0.005 and 2.500 mg/mL; the correlation coefficients ( r 2 ) ranged from 0.999 to 1; the limits of detection ranged from 0.013 to 0.033 μg/mL; and the relative standard deviations for repeatability, precisions, and stabilities were below 0.2%, 1.6%, and 0.6%, respectively. Conclusion: The results show that the method can be effective and comprehensive in evaluating the quality of PS from different origins. And this comprehensive strategy proved to be a powerful technique used to differentiate between different geographical herbs.